Tomografi Seismik Menggunakan Full Waveform Inversion Pada Studi Kasus Zona Kecepatan Rendah - Hidayat, Muhammad Akbar Najib; Capah, Ade I.G; Juniarto, Reinaldi (Jurnal Migasian, 2021)
This paper investigates near surface velocity imaging in the full waveform inversion (FWI). Conventional traveltime tomography may produce inaccurate result for imaging low velocity zone. FWI compute synthetic seismic shot gathers associated with initial velocity depth model by acoustic finite difference forward modeling. The velocity model is updated by iteratively back propagate waveform residual to update velocity model. This method is applied to synthetic 2-D land data which has complex structure and low velocity zone beneath the high velocity layer. We compare near-surface velocity models derived from traveltime tomography and FWI at simple model The result is traveltime tomography produces inaccurate result for low velocity anomaly in 2-D land synthetic seismic data, than FWI. In addition, FWI can further improve the near surface velocity model which shows greater vertical and lateral resolution and reveals low velocity zone that is not present in the traveltime tomography. Near surface imaging affects the result of static correction in preprocessing stage. More accurate near surface velocity model, more satisfied the result of static correction. The pre-stack time migration (PSTM) section using statics from FWI model led to more accurate time imaging results compared to PSTM section using traveltime tomography velocity model. Nowadays, in the oil and gas industry, the exploration of hydrocarbon is located in complex structure. FWI is a high-end method and needed to produce seismic image accurately.